Analisis Tantangan dalam Pengelolaan Sumber Daya Insani di Dinas Kebudayaan dan Pariwisata Kabupaten Banyuwangi untuk Peningkatan Pelayanan Publik - Siti Kamalia; Anisa Nur Indah Sari; Devi Hardianti Rukmana (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Human Resources (SDI) are non-material assets in an organization or company. Good Human Resource Management (SDI) / Human Resource Management (MSDI) has a positive impact on the quality of public services. A good work program will be hampered if the Human Resources within it are passive in carrying out their responsibilities. This is due to challenges that do not receive special attention from the Banyuwangi Culture and Tourism Office. The research method used in this research is a descriptive qualitative approach using interviews and in-depth observations of staff and employees of the Banyuwangi Culture and Tourism Office. Based on the results of observations, the challenges faced include limited resources, lack of training and development, lack of awareness and understanding of responsibilities, and piling up of individual tasks. The aim of this research is to provide solutions that can be implemented to face the challenges faced by the Banyuwangi Culture and Tourism Office.